2017
DOI: 10.3390/jmse5030043
|View full text |Cite
|
Sign up to set email alerts
|

Impact of North Atlantic Teleconnection Patterns on Northern European Sea Level

Abstract: Abstract:Northern European sea levels show a non-stationary link to the North Atlantic Oscillation (NAO). The location of the centers of the NAO dipole, however, can be affected through the interplay with the East Atlantic (EAP) and the Scandinavian (SCAN) teleconnection patterns. Our results indicate the importance of accounting for the binary combination of the NAO with the EAP/SCAN for better understanding the non-stationary drivers inducing sea level variations along the European coasts. By combining altim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 66 publications
(102 reference statements)
9
38
0
Order By: Relevance
“…Because the sea-level response to local wind and pressure changes in the North Sea is mostly barotropic in nature (e.g. Chen et al, 2014;Dangendorf et al, 2014a), the typical sea-level adjustment timescale to wind and pressure changes will not be longer than a few days (Dimon et al, 1997). However, the sea-level response to atmospheric forcing is mostly, but not necessarily fully barotropic in the North Sea (Tsimplis et al, 2006;Calafat et al, 2012), and local and large-scale atmospheric changes do not explain all variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the sea-level response to local wind and pressure changes in the North Sea is mostly barotropic in nature (e.g. Chen et al, 2014;Dangendorf et al, 2014a), the typical sea-level adjustment timescale to wind and pressure changes will not be longer than a few days (Dimon et al, 1997). However, the sea-level response to atmospheric forcing is mostly, but not necessarily fully barotropic in the North Sea (Tsimplis et al, 2006;Calafat et al, 2012), and local and large-scale atmospheric changes do not explain all variability.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the sea-level response to local atmospheric pressure variability along the British coast often deviates from the equilibrium inverse barometer effect, which has its likely cause in factors that co-vary with atmospheric pressure, such as wind-induced surges (Woodworth et al, 2009;Woodworth, 2017b). For the German and Dutch coast, a large part of the observed sea-level variability in the winter months can be explained by the North Atlantic Oscillation (NAO) (Wakelin et al, 2003;Yan et al, 2004), which mostly acts through local wind forcing (Chen et al, 2014). The NAO contains a strong multi-decadal component, which results in multi-decadal winter-mean sea-level variability in this region (Dangendorf et al, 2012).…”
mentioning
confidence: 99%
“…The SLP anomaly pattern associated with nutrient anomalies at the shelf break is best represented by a non-stationary combination of the North Atlantic Oscillation (NAO) and Scandinavian (SCAN) teleconnection patterns (Chafik et al, 2017). It also resembles the European-North Atlantic sector of the East Atlantic-west Russian pattern, a higher-order atmospheric mode of the Northern Hemisphere which occasionally mixes with the NAO (Barnston and Livezey, 1987;Fagherazzi et al, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Observational data have provided evidence for a significant increase in GIS mass loss during the recent decades (Luthcke et al, 2006;Vaughan et al, 2013;Chen, 2019). Modeling studies considered by the Fifth Assessment Report of the United Nations Intergovernmental Panel on Climate Change (IPCC AR5) agree that the GIS will continue to decrease in area and volume in a warmer climate as a consequence of increased melting rates not compensated by increased snowfall and amplified by positive feedbacks (Mikolajewicz et al, 2007;Collins et al, 2013;Church et al, 2013;Vizcaino et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Chafik et al [10] analyse how sea levels, observed along northern European coastlines, are affected and modulated by large-scale climate features. They detect a non-stationary sea-level response to the North Atlantic Oscillation (NAO), which is explained by the influence of the East Atlantic (EAP) and Scandinavian (SCAN) teleconnection patterns on the NAO.…”
Section: Mean Sea-level Changesmentioning
confidence: 99%